IDENTIFIKASI BATERI PENGIKAT TIMBAL (Pb) PADA SEDIEN DI PERAIRAN SUNGAI SIAK - Sri Wulandari; Nila Fitri Dewi; Suwondo ' (Biogenesis, 2005)
The research done to know bacteria type capable to fasten heavy metal lead (Pb) at sediment in territorial water of Siak River  Research procedure consist o f three phase that is; (1) Intake o f sediment sampel by purposive sampling random; (2) Isolation by grow sediment sampel at medium of Zobell 2216 E added with  PbNO3 and  of  Pb(CH3COOH)2 ;  (3)  Total  count  of  bacteria  and  identification  pursuant  to morphology form and biochemical test which cover; colony form, colony colour, colony size measure, cell form, coloration of gram, test katalase, test oksidase and  methyl red  Result of research indicate that total count of bacteria fastener o f heavy metal of lead (Pb) at sediment in territorial water o f Siak River range from 3,0 X  107 until  1,5 X  10s cell/ml and identified 6 bacterium type fastener of heavy metal of lead  (Pb)  that  is:  Micrococcuc,  Corynebacterium,  Phenylobacterium,  Enhydrobacter,  Morrcoccuss, Flavobacterium.   Key words : Bacteria fastener of heavy metal of lead ( Pb), identification, sediment